Tempo e fotografia: vertigem e paradoxo - Sanz, Cláudia Guilmar Linhares (2010)
The present time is increasingly saturated of photographs and has become devoid of duration. Accordingly, the temporal experience seems to be the central element by which the transformations of contemporary subjectivity are performed and this change is accompanied by a proper method of experimenting time through photographs. In order to think about the unprecedented dimensions of that experience it is necessary to undertake a historical retrocession and investigate the modern constitution of the interlacement between photography and time. From its beginning to the early decades of the twentieth century, it consisted of a kind of experience and ideal that in permanent transmutations, it ended by chasing coexistence of temporal tensions. Along this way it has become an amalgam of time, where in tension, mortal and eternal, discontinuity and continuity, heterogeneousness and homogeneity, relevance and irrelevance, happening and event, memory and remembrance, experience and its decline have coexisted.